Implementasi Pendekatan Pembelajaran Mendalam dalam Meningkatkan Kompetensi Profesional Guru - Bobby Jahroni Hartanto; Ali Nurdin; Suharyanto Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
The background of this research is based on the still dominance of learning practices that are oriented towards curriculum outcomes and surface learning outcomes, so that they have not fully encouraged conceptual understanding, reflection, and the meaning of learning. The deep learning approach is seen as a relevant strategy to answer these challenges because it emphasizes active engagement, critical thinking, and the association of knowledge with factual context. This study aims to analyze the implementation of the Deep Learning Approach in improving the professional competence of elementary school teachers. This researcher uses a case study approach with a qualitative research paradigm. The respondents in the study were the principal and teachers of SDN 2 Jatiluhur, Jatiluhur District, Purwakarta Regency. The data collection method was carried out through observation, in-depth interviews, and documentation studies. Data analysis is carried out interactively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that (1) the implementation of systematically managed deep learning contributes positively to the improvement of teachers' professional competence, especially in material mastery, reflective pedagogic skills, and the application of authentic assessment; (2) This approach encourages the creation of more meaningful and humanistic learning. The conclusion of the research is that deep learning supported by effective school management can be a sustainable strategy in improving teacher professionalism.